Bioaccessibility and Pharmacokinetics of a Commercial Saffron (Crocus sativus L.) Extract. (31st January 2020) - Almodóvar, Paula; Briskey, David; Rao, Amanda; Prodanov, Marín; Inarejos-García, Antonio M.
Abstract : There are few studies about the pharmacokinetics of the low-molecular mass carotenoids crocetin or crocin isomers from saffron ( Crocus sativus L.). None has been performed with a galenic preparation of a standardised saffron extract. The aim of the present research work was to study the effect of in vitro digestion process on the main bioactive components of saffron extract tablets and the corresponding pharmacokinetic parameters in humans. Pharmacokinetics were calculated collecting blood samples every 30 min during the first 3 h and at 24 h after administration of two different concentrations (56 and 84 mg of the saffron extract) to 13 healthy human volunteers. Additionally, an in vitro digestion process was performed in order to determine the bioaccessibility of saffron main bioactive compounds. Identification and quantification analysis were performed by HPLC-PAD/MS. Digestion resulted in 40% of bioaccesibility for crocin isomers, whereas, safranal content followed an opposite trend increasing about 2 folds its initial concentration after the digestion process. Crocetin in plasma was detected in a maximum concentration ( C max ) in blood between 60 and 90 min after oral consumption with dose-dependent response kinetics, showing that crocin isomers from galenic preparation of saffron extract are rapidly transformed into crocetin. The results showed that this tested galenic form is an efficient way to administer a saffron extract, since the observed crocetin C max was similar and more quickly bioavailable than those obtained by other studies with much higher concentrations of crocetin.